Milwaukee WPA Handicraft Project Online Exhibit - (:unkn) unknown (My University, 2012)
This online presentation provides photographs and text from an exhibit prepared by the late Mary Kellogg Rice for the Golda Meir Library in October 1997. Rice served as art director for a highly regarded WPA project operating in the 1930s for women in Milwaukee County. The historic WPA photographs and examples of project work were collected by Rice for her book “Useful Work for Unskilled Women: A Unique Milwaukee WPA Project,” published by the Milwaukee County Historical Society in 2003. Rice dedicated the exhibit to the five thousand women and men who worked for the Milwaukee Handicraft Project from 1935 to 1943. She wrote, “These individuals were forced onto public relief to aid their families during the Great Depression. While they often used inexpensive materials and initially lacked employment skills, the workers made products of outstanding quality, beauty and education value. Their work enriched the lives of children and adults in schools, nurseries, state and county institutions, hospitals and colleges in Milwaukee County and throughout the nation.” Eleven production units were eventually established for bookbinding, blockprinting, screenprinting, weaving, rugs, appliqués, dolls, cloth toys, costumes, wood toys and furniture.
Keywords: WPA; work relief; Great Depression; 1930s; history